In meeting the increasing demands for total knee arthroplasty, can we achieve high levels of quality care in a small community hospital? A mixed-methods study - Sanders, Ethan B.; Dobransky, Johanna S.; Chen, Brian P.; Bodrogi, Andrew W.; , on behalf of Ottawa Arthroplasty Group; Beaulé, Paul E.; Poitras, Stéphane (Frontiers in Surgery, 2023)
Purpose: Small community hospitals (SCH) help to address the demand for total knee arthroplasty (TKA). This mixed methods study compares outcomes and analyses environmental differences following TKA at a SCH and tertiary care hospital (TCH). Methods: Quantitative: A retrospective review of 352 propensity matched primary TKAs at both SCH and TCH, based on age, BMI and ASA class was completed. Groups were compared by length of stay (LOS), 90-day Emergency Department visits, 90-day readmissions, reoperations, and mortality. Qualitative: Based on the Theoretical Domains Framework seven prospective semi-structured interviews were performed. Interview transcripts were coded and belief statements were generated and summarized by two reviewers. Discrepancies were resolved by a third reviewer. Results: Quantitative: The average LOS for the SCH was significantly shorter than that of the TCH (2.0+/-0.2 vs. 3.6+/-2.7 days; p < 0.001), a difference that persisted following subgroup analysis of ASA I/II patients (2.0+/-0.2 vs. TCH 3.2+/-2.2; p < 0.001). There were no significant differences in other outcomes. Qualitative: The main themes surrounded a higher case load for physiotherapy at the TCH resulted in patients waiting longer to be mobilized after surgery. Patient disposition also affected patient discharge. Conclusion Given the increasing demand for TKA, SCH represents a viable option increase to capacity, while reducing LOS. Future directions to reduce LOS include addressing social barriers to discharge, and patient prioritization for assessment by allied health. When performed by the same surgeons, the SCH provides comparable quality of care with a shorter LOS, due to resource utilization differences.